Keratin/chitosan film promotes wound healing in rats with combined radiation-wound injury - Yu-mei Wang; Tong Xin; Hao Deng; Jie Chen; Shen-lin Tang; Li-sheng Liu; Xiao-liang Chen (Journal of Materials Science: Materials in Medicine)
Abstract Human hair keratin, a natural protein derived from human hair, has emerged prominently in the field of wound repair, showcasing its unique regenerative capabilities and extensive application potential. However, it is a challenge for the keratin to efficiently therapy the impaired wound healing, such as combined radiation-wound injury. Here, we report a keratin/chitosan (KRT/CS) film for skin repair of chronic wounds in in rats with combined radiation-wound injury. In brief, the KRT/CS film was characterized by scanning electron microscopy (SEM), mechanical property analysis, water absorption, and swelling analysis. A rat model of combined radiation-wound injury was employed to evaluate the therapeutic efficacy of the KRT/CS film. Finally, the systemic biotoxicity of KRT/CS film was assessed through histological analysis. The surface of KRT/CS film was uniform and smooth compared with the KRT film, and the mechanical property, swelling rate and water absorption rate of KRT/CS film were significantly improved, which can meet the application requirements of wound excipient dressing. Furthermore, the combined radiation-wound injury in rats was established that the wound closure rate was achieved 74.46% after 14 days of treatment with KRT/CS film, comparing to the single KRT membrane and commercially available Band-Aids. Histological analysis demonstrated that the amount of angiogenesis and collagen deposition in wounds treated with KRT/CS were significantly improved. These findings demonstrate the KRT/CS film as a promising therapeutic agent for combined radiation-wound injury. Graphical Abstract